Chapter La mediazione di mattering e senso di comunità nella relazione tra partecipazione e benessere - PARADISI, MONICA (Firenze University Press, 2025)
The aim of the present study is to analyse the mediating role of perception of mattering to family and friends, as well as the sense of community in the association between participation (volunteering and recreational activities) and subjective well-being. An online questionnaire was administered to 273 Italian adults. Results support the mediating role of mattering to family in the association between volunteering and well-being; the mediating role of mattering to friends in the relationship between recreational activities and well-being; and finally, a sequential mediation of sense of community and mattering towards friends in the link between volunteering and well-being. The findings suggest how different types of participation interact differently with well-being promotion factors, such as the sense of community and mattering.